Desain Electrical Submersible Pump (ESP) Untuk Meningkatkan Laju Alir Produksi Pada Sumur “DT014” - Iin Darmiyati; Della Endangtri; Firdaus; Rohima Sera Afifah; Abdul Gafar Karim; Fatma; Muhammad Alif; Pratama Bagus Restu.S (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Oil production from a well often decreases due to reduced reservoir pressure, so a production increase method or artificial lift is needed to maintain or increase the production flow rate. One of the commonly used artificial lift methods is the Electrical Submersible Pump (ESP). This study aims to design an optimal ESP system for the DT014 well, which is experiencing decreased production. The analysis was carried out by considering reservoir parameters, fluid characteristics, and well operating conditions. The design process includes the selection of pumps, motors, and electrical cables that are in accordance with production needs. Simulations were carried out to ensure the performance of the ESP in increasing oil production efficiently and economically. The design results show that the application of ESP to the DT014 well can significantly increase the production flow rate compared to previous methods. By considering pump efficiency and energy consumption, the selection of the right ESP can maximize production while minimizing operational costs. Thus, the implementation of ESP has proven to be an effective solution to increase oil production in wells experiencing decreased reservoir pressure. This study is expected to be a reference for the optimization of artificial lift systems in oil fields with similar conditions.